Dampak Positif Program Makan Bergizi Gratis (MBG) bagi Siswa : Studi Literatur - Dyah Ayu Nur Aini; Rio Ramadhan Setiawan; Jick Prasetyo Wicaksono; Gaitsa Zahira Shafira; Nazwa Isfalana Idris (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
As a strategic public policy, the Free Nutritious Meal program serves as a long-term social investment aimed at enhancing the quality of human resources. This study is directed to examine and map the positive contributions of the MBG initiative to the pillars of health, discipline levels, and academic achievement of students through a literature review method. The article search, utilizing keywords such as "Makan Bergizi Gratis," "Implementasi MBG," and "Dampak MBG," yielded 10 relevant scientific articles, which were subsequently analyzed using thematic analysis techniques. The findings indicate that the MBG program exerts a significant positive impact on various dimensions of student development. In the academic aspect, this program improves students' focus, concentration, motivation, and active learning engagement. Health-wise, MBG contributes to improving nutritional status, which supports children's physical and psychological readiness, whereas, in terms of discipline, this intervention is proven to increase attendance rates while reducing tardiness at school. Overall, it is concluded that the MBG program does not merely function to fulfill essential nutritional intake, but also acts to maximize learning effectiveness and student academic performance across all education levels.